An Agent-Based Model for Optimization of Road Width and Public Transport Frequency - Mark E. Koryagin (Promet (Zagreb), 2015)
An urban passenger transportation problem is studied. Municipal authorities and passengers are regarded as participants in the passenger transportation system. The municipal authorities have to optimise road width and public transport frequency. The road consists of a dedicated bus lane and lanes for passenger cars. The car travel time depends on the number of road lanes and passengers’ choice of travel mode. The passengers’ goal is to minimize total travel costs, including time value. The passengers try to find the optimal ratio between public transport and cars. The conflict between municipal authorities and the passengers is described as a game theoretic model. The existence of Nash equilibrium in the model is proved. The numerical example shows the influence of the value of time and intensity of passenger flow on the equilibrium road width and public transport frequency.